THE IMPACT OF CAREER PLANNING,SELF EFFICACY AND HARD SKILL ON JOB READINESS AMONG UNDERGRADUATE STUDENTS: A CASE STUDY AT STIE TOTALWIN SEMARANG - Lova, Aron Martha; Kiswoyo, Kiswoyo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to identify and evaluate in depth the impact of career planning, self-efficacy, and hard skills possessed by students on job readiness. Methods: The study population consisted of 219 students, and 70 of them were selected as the sample, calculated using the Slovin formula. Data were collected through questionnaires and processed using the SPSS program with the application of multiple linear regression models. Results: This research reveals a positive impact and significant influence of Career Plan on job readiness, with a significance value greater than 0.05, namely (0.000 > 0.05). Self-efficacy does not have a strong enough direct influence on job readiness, with a significance value> 0.05, which is not fulfilled, namely (0.140 < 0.05). Hard Skill has a positive impact and significant effect on job readiness, with a significance value> 0.05 fulfilled, namely (0.000> 0.05).